2014
DOI: 10.11120/elss.2014.00026
|View full text |Cite
|
Sign up to set email alerts
|

Researcher-led Training: the PhD Experience Conference 2013 – Supporting the Student in Higher Education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There exist various training programmes aimed at developing doctoral supervision skills, reflected in institutional websites and training institutions, in line with the views of Halse (2011) and Lee (2018). While some are offered during the doctoral process (Wadee et al, 2010), others are offered within structured institutional training programmes (Lee, 2018) and through participating in conferences (Costello, Waehning, Reed, & Shaw, 2013). Postdoctoral studies, mentorship and graduate training programmes have also been reported to enhance the development of doctoral supervision skills as well as preparing doctoral graduates for academic positions (Åkerlind, 2005;Wadee et al, 2017;Lee, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…There exist various training programmes aimed at developing doctoral supervision skills, reflected in institutional websites and training institutions, in line with the views of Halse (2011) and Lee (2018). While some are offered during the doctoral process (Wadee et al, 2010), others are offered within structured institutional training programmes (Lee, 2018) and through participating in conferences (Costello, Waehning, Reed, & Shaw, 2013). Postdoctoral studies, mentorship and graduate training programmes have also been reported to enhance the development of doctoral supervision skills as well as preparing doctoral graduates for academic positions (Åkerlind, 2005;Wadee et al, 2017;Lee, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of discipline, candidates also tend to struggle at pivotal academic points which resonate with generic threshold concepts in research -argument framing; theorising; research framework development; knowledge creation; analysis and interpretation; and, paradigm building (Kiley & Wisker, 2009) -and these pivotal points are not always successfully addressed within the candidate/supervisor relationship (Bruce et al, 2009;Bruce & Stoodley, 2013;Hamilton et al, 2014;Platow, 2012;Yarlagadda et al, 2013). These are, moreover, academic issues and concerns that need to be addressed by academic learning and teaching, rather than generic/generalist training and approaches (Costello, Waehning, Reed, & Shaw, 2014;Craswell, 2007).…”
Section: Promoting Conceptual Integration: Using Threshold Concepts As a Pedagogical Rationalementioning
confidence: 99%
“…al 2014. They are, moreover, academic issues and concerns that need to be addressed by an approach to learning and teaching that is academic, rather than generic generalist training (Craswell 2007, Costello et al 2014.…”
Section: Multidisciplinary and Interdisciplinary Research Trainingmentioning
confidence: 99%